Entre saberes e fazeres: uma investigação sobre o racismo e o antirracismo nas práticas de terapeutas ocupacionais - Pereira, Amanda dos Santos (Universidade Federal de São Carlos, 2026)
Occupational therapy practitioners have neglected to address the racism that is sustained and reproduced in therapeutic practices. While discussions on ethnic-racial issues have grown in the field in recent years, few studies investigate the theoretical and methodological frameworks that inform the practices of occupational therapy practitioners who work with Black populations and traditional peoples and communities. This study aims to identify, describe, and reflect on the experiences of occupational therapy practitioners working with Black populations and traditional peoples and communities. The specific aims of this study are: 1. To understand how occupational therapy practitioners have provided service to Black populations and traditional peoples and communities; 2. To map the practices of occupational therapy practitioners that address ethnic-racial issues in their therapeutic practices; 3. To identify the conceptual and methodological frameworks that guide the practices of occupational therapy practitioners with Black populations and traditional peoples and communities; 4. To explore the possibilities, limitations, strategies, perceptions, and challenges faced by occupational therapy practitioners in this field of practice; 5. To review the existing knowledge in the literature about how occupational therapy practitioners can take antiracist actions in professional practice. This study was developed by a qualitative approach associated with visual methodologies, using photo-elicitation and semi-structured interviews as data generation instruments. The perspective of Afro-Latin American feminism also informs the methodology of this work. The data were obtained from narratives and photographs produced by six occupational therapy practitioners who develop research, teaching, or intervention with Black people and/or with traditional peoples and communities. The data were analyzed through thematic analysis, resulting in four themes: 1st Theme – Becoming Black: Identity, existential territories, and belonging; 2nd Theme –Academic training and epistemic dispute; 3rd Theme – Racism and its impacts on occupational therapy practices; 4th Theme – The future is here and now! Afrofuturist perspectives. The researcher partners' narratives evidence shows that the presence of institutional and epistemological violence, manifested in the lack of attention to address racism in work teams, the absence of ethnic-racial issues in occupational therapy training, the centrality of Eurocentric curricula, and the negligence in the formulation and implementation of public policies. The researcher partners argue that racism makes the Black population and traditional peoples sick, constituting a direct producer of psychological suffering and social exclusion. Furthermore, they present anti-racist strategies aimed at reorienting the practice of occupational therapy, with a view to strengthening identity, cultural recognition, valuing Blackness, self-esteem, and belonging. From an Afrodiasporic and Afro-Latin American perspective, this study proposes counter-hegemonic strategies and frameworks capable of supporting research, teaching, and the provision of socially relevant services for these populations.
Between knowledge and practice: an investigation into racism and anti-racism in the practices of occupational therapists.
Keywords: Terapia ocupacional; População negra; Povos tradicionais; Antirracismo; Occupational therapy; Black population; Traditional peoples; Antiracism; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 18. Igualdade Étnico-Racial para o Desenvolvimento Sustentável